Analisis Jumlah Septic Tank Pekecamatan Di Kota Pekanbaru - Syafrida Khairani; Aryo Sasmita; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
A septic tank is a room or several waterproof rooms that function to collect or treat wastewater. The purpose of this study was to know how many of septic tank users in each district in the city of Pekanbaru on 2018. Pekanbaru has 12 districts with a total of 254.263 householders and the septic tank users as many as 225.622 units. The result show that the most in the Tampan sub-district, totaling 50.840 and at least in the Sail sub-district, totaling 4,749. Keywords: Septic Tank, Sub-district, Tampan, Sail